MODEL PENDAMPINGAN BERBASIS MASALAH UNTUK PERCEPATAN AKREDITASI JURNAL ILMIAH DI PERGURUAN TINGGI KEAGAMAAN ISLAM SWASTA (PTKIS) - Abidin, Zaenal; Khalik, Subehan; Nisa Nuur, Khaerun (JURNAL KHAZANAH PENGABDIAN, 2025)
The limited readiness of journal management systems within several Islamic Higher Education Institutions (PTKIS) in South Sulawesi has hindered many journals from meeting the national SINTA accreditation standards. Common issues include weak editorial governance, irregular publication schedules, insufficient editorial capacity, and suboptimal utilization of the Open Journal Systems (OJS). This community service program aims to enhance the accreditation readiness of five PTKIS journals through a problem-based mentoring approach. The method involved a preliminary assessment, root-problem identification, action-plan development, technical training, intensive mentoring, and evaluation based on governance indicators and accreditation document completeness. The mentoring was conducted for five journals: JISH (SINTA 5), Bustanul Fuqaha (SINTA 4), Wahatul Mujtama’ (SINTA 5), AILREV (SINTA 4), and Al-Ahkam (SINTA 5). The results demonstrate significant improvements in editorial governance, publication consistency, template standardization, accreditation documentation, metadata quality, DOI integration, and compliance with publication ethics. All journals showed increased preparedness for accreditation submission and improved fulfillment of SINTA indicators. The implications of this program highlight the effectiveness of problem-based mentoring as a capacity-building model for PTKIS journals and reinforce its potential for broader replication in strengthening the quality of scholarly publishing across academic institutions.